DETERMINATION OF COMPANY VALUE IN THE ENERGY AND BASIC MATERIAL SECTOR - Frengki Putra Ramansyah; Rico Nur Ilham (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
This research investigates the determinants of company value within the Energy and Basic Materials sectors listed on the Indonesia Stock Exchange (IDX) from 2021-2023. It examines the impact of Carbon Emission Disclosure (CES), Green Innovation (IH), Environmental, Social, and Governance (ESG), Eco-efficiency (EFI), and Environmental Performance (KL) on Tobin's Q as a measure of company value. The analysis, employing panel data regression with a Fixed Effect Model (FEM), reveals that while ESG, EFI, and KL positively influence company value, CES has a negative impact, and IH shows an insignificant effect. These findings provide insights for companies aiming to enhance their market value by prioritizing environmental and social responsibility.